Drivers of New Business Creation in the OECD: The Role of Education and Taxation - António Afonso; M. Carmen Blanco-Arana; Ana J. Cisneros-Ruiz (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
The main aim of this paper is to empirically assess the impact of education and tax revenue onfostering new business creation in the OECD countries. To this end, we employ fixed effects and random effects models using panel data from 2006 to 2022, incorporating alternative conditions. Results confirm that while education and the economic situation are key pillars in fostering new business creation, the role of tax revenue in supporting economic development – and, by extension, new business formation – is fundamental, even if non-linear, with a threshold of 30% of GDP. Tax revenue collected by governments provides essential funding for public goods and services such as infrastructure, education, and innovation support programs, all of which contribute to creating an environment where new businesses can emerge and thrive. Our findings remain robust under the GMM estimation.
Keywords: C23; H2; I2; M20; 330; new business; tax revenue; education; economic growth; panel data